Post Weld Heat Treatment affecting Mechanical Properties of Hard-faced Weld Metal on Carbon Steel Surface - Yaemphuan, Paiboon; Wattanajitsiri, Voraya; Kimapong, Kittipong (Journal of Advanced Development in Engineering and Science, 2023)
Hard-facing welding was one of the maintenance processes for improving the agricultural machine part. However, the welding always produced an identical mechanical property between a welded metal and a base metal. So, if the welded specimen was heat- treated, the mechanical property of the welded specimen might be improved. This research aimed to comparative study of the specimen mechanical property of the pre- and post- weld heat treatment. The summarized results were as follows. The heat treatment of the weld metal that produced at low welding current of 90A produced a crack in the weld metal. The post weld heat treatment affected to decrease the hardness and the wear resistance of the hard-facing weld metal. Wear resistance of the heat treated specimen was lower than that of the as-welded specimen and was about 0.71%.